Utilizing Story Mapping Strategy to Improve Students' Reading Comprehension in Finding Main Idea (NOBEL: Journal of Literature and Language Teaching, 2018)
This research aims at (1) finding out whether Story Mapping Strategy can improve students' reading comprehension in finding main idea and (2) describing classroom climate when Story Mapping Strategy is implemented in the class. The preliminary research showed that the students had problems in determining main idea of the text and main idea in each paragraph and in finding the supporting details of the main idea in each paragraph. This research was conducted at SMA Kemala Bhayangkari 1 Jakarta. The subject of the research was the students of class XI IPA 1 consisting of 30 students. The method of this research was Classroom Action Research and it was conducted in three cycles. Each cycle covered planning, implementing, observing, and reflecting. In collecting the data, the researcher used observation field note, interview, questionnaire, diary, and test. Having collected the data, the researcher analyzed quantitative and qualitative data. The quantitative data were analyzed by using descriptive statistic (DS). It compared between the mean score of pre-test (before treatment) and post-test 1, 2, and 3 (after treatment). The qualitative data were analyzed by using Constant Comparative Method (CCM) which consisted of comparing incidents applicable to each category, integrating categories and their properties, delimiting the theory, and writing the theory. The result of the research showed that (1) Story mapping strategy can improve the students' reading comprehension in finding main idea in terms of: (a) the students can determine the main idea of the text and main idea in each paragraph and (b) the students can find the supporting details of the main idea in each paragraph. The means of the students' score improved from cycle to cycle. The mean in pre-test: 62.33, post-test 1: 68.33, post-test 2: 72.78, and post-test 3: 77.89 compared with the KKM for reading: 70. (2) Story mapping strategy can improve the classroom climate in terms of: the students' cooperation looked maximal and alive, (b) the researcher as a teacher gave the students more motivation, help, support, and encouragement maximally, (c) all of the students looked more enthusiastic and got custom in story mapping and main idea activity, (d) all of the students could participate well in classroom activity, and (e) most of the students thought that the researcher as a teacher often gave them praise or appreciation in classroom activity Key Words; Story mapping strategy, Reading comprehension, Main Idea, Action Research